Clinical usefulness of oxygen uptake during usual gait in patients with cardiovascular disease. (15th July 2021) - Hamazaki, Nobuaki; Kamiya, Kentaro; Nozaki, Kohei; Yanagi, Naoya; Ichikawa, Takafumi; Matsuzawa, Ryota; Nakamura, Takeshi; Yamashita, Masashi; Uchida, Shota; Saito, Teppei; Maekawa, Emi; Meguro, Kentaro; et al.
Abstract: Background: Although oxygen uptake (VO2 ) during exercise stress is a surrogate marker for prognosis in patients with cardiovascular disease (CVD), the stress test is sometimes difficult to perform owing to patient conditions, such as ageing or comorbidities. We investigated the relationships between VO2 during usual gait with physical function and prognosis in patients with CVD. Methods: This single-centre observational study enrolled consecutive patients who were hospitalized for CVD treatment. Isometric quadriceps strength (QS) and 6-min walk distance (6MWD) as physical functions, and VO2 during usual gait speed were measured at hospital discharge. We assessed the changes in VO2 per body weight between at rest and during gait divided by gait speed (VO2 /kg/gait) and analysed the relationships of VO2 /kg/gait with physical functions and composite incidences of all-cause death or unplanned readmission after discharge. Results: In 367 patients (age, 65 ± 13 years; females, 34%), 112 clinical events occurred. VO2 /kg/gait showed significant negative correlations to QS (β = −0.114, p = 0.024) and 6MWD (β = −0.163, p < 0.001) after adjusting for confounding factors. High VO2 /kg/gait was significantly associated with a high rate of clinical events (hazard ratio for 1 standard deviation of VO2 /kg/gait, 1.36; 95% confidence interval, 1.11–1.66). This association was also observed in subgroups of older age and frailty. Conclusions: High VO2 during usual gait was a relevant factor for low physical function and poor prognosis in patients with CVD and even in older age and frailty, meaning that VO2 during usual gait might be a novel and useful marker in clinical practice. Graphical abstract: Unlabelled Image Highlights: VO2 during usual gait is an indicator of movement efficiency. We examined the clinical usefulness of VO2 during usual gait in patients with CVD. A high VO2 during gait correlated with low physical function and high incident rate. High gait VO2 correlated with a poor prognosis in subgroups of older age and frailty. VO2 during gait is a useful marker that is relevant to physical function and prognoses in CVD.